Diagnostic Yield of Genetic Testing in Young Athletes With T-Wave Inversion. Issue 12 (18th September 2018) - Sheikh, Nabeel; Papadakis, Michael; Wilson, Mathew; Malhotra, Aneil; Adamuz, Carmen; Homfray, Tessa; Monserrat, Lorenzo; Behr, Elijah R.; Sharma, Sanjay
Abstract : Background: T-wave inversion (TWI) is common in patients with cardiomyopathy. However, up to 25% of athletes of African/Afro-Caribbean descent (black athletes) and 5% of white athletes also have TWI of unclear clinical significance despite comprehensive clinical evaluation and long-term follow-up. The aim of this study was to determine the diagnostic yield from genetic testing, beyond clinical evaluation, when investigating athletes with TWI. Methods: We investigated 50 consecutive asymptomatic black and 50 white athletes 14 to 35 years of age with TWI and a normal echocardiogram who were referred to a UK tertiary center for cardiomyopathy and sports cardiology. Subjects underwent exercise testing, 24-hour ambulatory ECG, signal-averaged ECG, cardiac magnetic resonance imaging, and a blood-based analysis of a comprehensive 311-gene panel for cardiomyopathies and ion channel disorders associated with TWI, including hypertrophic cardiomyopathy, arrhythmogenic right ventricular cardiomyopathy, dilated cardiomyopathy, left ventricular noncompaction, long-QT syndrome, and Brugada syndrome. Results: In total, 21 athletes (21%) were diagnosed with cardiac disease on the basis of comprehensive clinical investigations. Of these, 8 (38.1%) were gene positive (myosin binding protein C[ MYBPC3 ], myosin heavy chain 7 [ MYH7 ], galactosidase alpha [ GLA ], and actin alpha, cardiac muscle 1 [ ACTC1 ] genes) and 13 (61.9%) were gene negative. Of the remaining 79 athletes (79%), 2 (2.5%) were gene positive (transthyretin [ TTR ] and sodium voltage-gated channel alpha subunit 5 [ SCN5A ] genes) in the absence of a clinical phenotype. The prevalence of newly diagnosed cardiomyopathy was higher in white athletes compared with black athletes (30.0% versus 12%; P=0 .027). Hypertrophic cardiomyopathy accounted for 90.5% of all clinical diagnoses. All black athletes and 93.3% of white athletes with a clinical diagnosis of cardiomyopathy or a genetic mutation capable of causing cardiomyopathy exhibited lateral TWI as opposed to isolated anterior or inferior TWI; the genetic yield of diagnoses from lateral TWI was 12.3%. Conclusions: Up to 10% of athletes with TWI revealed mutations capable of causing cardiac disease. Despite the substantial cost, the positive diagnostic yield from genetic testing was one half that from clinical evaluation (10% versus 21%) and contributed to additional diagnoses in only 2.5% of athletes with TWI in the absence of a clear clinical phenotype, making it of negligible use in routine clinical practice. Abstract : Supplemental Digital Content is available in the text.